Effects of COVID-19 on English Language Education: A Postcolonial Perspective - Gupta, Puja Kumari (GS WOW: Wisdom of Worthy Research Journal, 2025)
This postcolonial thematic research examines the effects of the COVID-19 pandemic on English language instruction in South Asia from a postcolonial perspective. The study, based on a review of peer-reviewed literature, delineates five predominant themes: teacher resilience and adaptability, technology utilization and the digital divide, innovative and inclusive pedagogical practices, socio-cultural and institutional challenges, and the emotional and psychological impacts on language learners. The results show that the effects of colonialism are still felt in South Asian education institutions, making it harder for rural and vulnerable groups to get access to digital infrastructure, culturally relevant learning resources, and fair teaching methods. The pandemic led to significant instructional innovations and adaptability among educators; nevertheless, deeply rooted socio-cultural views and institutional limitations hindered the permanence of transformative change. The research emphasizes the necessity for culturally responsive and decolonized English language teaching changes in the post-pandemic context to rectify systematic injustices, foster inclusivity, and elevate the voices of historically oppressed students.